Loss Mitigation Strategies in Sharia Commericial Banks in Indonesia - Anggraini, Putri Pindia; Sahroni, Abdullah; Jamil, Mahmud Alfan; Susilo, Adib (IAIN Manado, 2024)
This research aims to determine the effect of Profit-Sharing Financing, Financing to Deposit Ratio (FDR), and Non-Performing Financing (NPF) on Profitability because there are several deviations in theory and there are still ratios in variables that do not comply with standards so this research is needed. This type of research is quantitative using secondary data. The population of this research is Sharia Commercial Banks in Indonesia and there are 9 samples selected using the purposive sampling method. The data analysis techniques used are descriptive statistics, panel data regression test, classical assumption test, hypothesis test and coefficient of determination using the Eviews 12 application. The results of this research show that partially the Profit Sharing Financing variable has no effect on the Profitability of Indonesian Sharia Commercial Banks, the Financing to Deposit Ratio (FDR) variable has a significant effect on the Profitability of Indonesian Sharia Commercial Banks, the Non Performing Financing (NPF) variable has no effect on the Profitability of Indonesian Sharia Commercial Banks, and simultaneously Profit Sharing Financing, Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) has a significant effect on the Profitability of Indonesian Sharia Commercial Banks. Profit Sharing Financing in this period is considered still low so it cannot influence the Profitability variable and the Profitability variable can be influenced by other financing. A balanced or high FDR can reflect efficiency in managing funds. using customer savings funds, so that banks can reduce their capital costs, which affects the ups and downs of profit margins and profitability, and effective risk management is one of the reasons why NPF has no effect on profitability.